A questão da linguagem em Martin Heidegger : entre a técnica e a serenidade - Nascimento, José Vander Vieira do (2017)
The present research seeks to understand the issue of language in Martin Heidegger's thinking, questioning the way it is considered by the technical world in order to think of a change in our relationship with the language that allows us to consider it in an original or natural way. Such a change consists of thinking of a way of considering language that differs diametrically in the way we consider it in the age of technique, so that we can gain its original, non-technical dimension, which also provokes a criticism that rethinks all the way we deal with things and with our way of being-in-the-world, a mode which is given mainly under such technoscientific thinking. It is necessary a change of thought, which goes beyond the calculating and objective scope of the technique towards a thought that meditates and reflects and which, in this way, takes place serenely. It is from the attitude that Heidegger calls "serenity towards things," a way of inhabiting this earth and of relating to the whole of entes from the thought that meditates and that lingers over things, that we can rethink our way of life - based on a prior conception of the reality that is conceived from an enframing that makes it available - to think of a possibility of inhabiting our land poetically and serenely.